Secondary Syphilis Reinfection with Suspected Asymptomatic Neurosyphilis - Mahono, Charles Kurnia; Niode, Nurdjannah Jane (Indonesian Journal of Case Reports, 2023)
Syphilis, a sexually transmitted disease caused by Treponema pallidum, poses a significant global health threat, with an annual incidence of around 12 million cases, predominantly affecting individuals aged 15-49. Reinfection occurs in 11 out of 120 patients, underscoring the importance of effective management. If untreated, 4-9% of cases may progress to early neurosyphilis, often presenting asymptomatically. We present the case of a 22-year-old male with reddish-brown patches on the face, palms, and soles, along with erythematous papules on the genital region, following a history of recent promiscuity. Physical examination revealed distinctive manifestations, including nickels and dimes on the face, syphilitic roseola, Biett's collarette on the palmoplantar region, and erythematous papules-plaques on the scrotal and penile areas. The VDRL test indicated a titer of 1:32, TPHA test >1:5120, and a non-reactive HIV rapid test. Initiating treatment with a single intramuscular injection of benzyl benzathine penicillin G (2.4 million IU) resulted in successful symptom resolution, accompanied by a four-fold decrease in VDRL titer to 1:8 by the third month. However, a subsequent increase to 1:32, following sexual intercourse in the sixth month, indicated reinfection and raised suspicions of asymptomatic neurosyphilis. The patient received oral doxycycline (100 mg twice daily) for 30 days. Unfortunately, treatment success could not be determined as the patient was lost to follow-up. This case report highlights that elevated VDRL titers signify reinfection, treatment failure, or neurosyphilis. Asymptomatic reinfection is common due to lead-time bias and partial immunity, especially with multiple episodes of syphilis. Early neurosyphilis may coexist with primary or secondary syphilis and is frequently asymptomatic. Continued efforts in monitoring and treatment adherence are crucial for effective syphilis management on a global scale.